Flowing Based on a Novel by Aya Koda - Naruse, Mikio; Tamai, Masao; Tanaka, Kinuyo; Yamada, Isuzu; Takamine, Hideko (Eureka Video, 2006)
Directed in 1956, the year that prostitution was outlawed in Japan, "Flowing explores the inner workings of a changing world, as traditional geishas faced the impending decline of their hidden way of life and the looming spectre of prostitution. It depicts the story of a widow, Rika (Kinuyo Tanaka), who is forced to work for a living and becomes a maid in a struggling Tokyo geisha house where its proud mistress (Isuzu Yamada) tries to save the house from becoming either a restaurant or a brothel. It is through Rika that we are introduced to the various geishas, who drink and fight, worry over the lack of clients, and attempt to stave off imminent extinction. Based on a book by Koda Aya, "Flowing" is a showcase for both Naruse's powers of empathy, and his natural talent in constructing complex female characters on-screen. The result is one of the most innovative and revealing of all geisha films. [Cover]
Keywords: DVD-Video